Pengembangan E-LKPD Berbasis FLIPBOOK pada Pembelajaran Akuntansi Kelas XI SMKN 4 Jember - Sholehah, Riska Maratus; Kartini, Titin; Herlindawati, Dwi (Universitas Galuh, 2024)
The integration of technology is one of the impacts of modern developments that is felt during the learning process. These changes require educators to continue to innovate by optimizing the use of ICT starting from preparing learning tools to the evaluation process. One of the learning tools that educators need to prepare well is LKPD. LKPD is a learning support and facility to support learning activities and student performance. At SMKN 4 Jember the LKPD used is still conventional. The use of conventional LKPD is considered less interesting and makes students feel bored and thus creates boredom in learning. The aim of this research is to produce flipbook-based digital LKPD that is feasible and attractive in terms of material and design. The research uses the ADDIE development model which consists of five stages, namely (1) analyze, (2) design, (3) development, (4) implementation, and (5) evaluation. The assessment instruments used are material expert validation sheets, design experts and student response questionnaires. This development research only reached the development stage because the aim of this research was to produce a flipbook-based LKPD product and test the feasibility of the product. Product feasibility is assessed in terms of material and design, with each involving 2 validators. The test subjects in this research were 34 students from class. The media attractiveness score in the broad group trial was 82,4%, included in the